Hydrothermal synthesis of rGO-PbBi2Se4 composite and investigation of its structural, chemical and field emission properties - Aher, Rahul; Bhorde, Ajinkya; Sharma, Priyanka; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Rondiya, Sachin; Chaudhary, Minakshi; Gopinath, Chinnakonda; Suryawanshi, Sachin; More, Mahendra; Jadkar, Sandesh (Journal of Materials Science-Materials in Electronics, 2018)
In the present study we report the one step facile synthesis of pristine lead bismuth selenide (PbBi2Se4) and reduced graphene oxide (rGO) and its composites with PbBi2Se4. Formation of pristine PbBi2Se4 and rGO-PbBi2Se4 composite were confirmed by X-ray diffraction and X-ray photoelectron spectroscopy. The surface morphology and topography investigated by using scanning electron microscopy and transmission electron microscopy revealed the formation of nano-flowers pristine PbBi2Se4. After coupling pristine PbBi2Se4 with rGO the surface morphology shows the formation of sharp vertically protruded nano-sheets/nano-flaks originated from the nano-flowers. Finally, the field emission properties of pristine PbBi2Se4 and rGO-PbBi2Se4 composite have been investigated. It has been observed that the rGO-PbBi2Se4 composite emitter exhibited excellent field emission properties with low turn-on field (similar to 2.8 V/A mu m for 10 A mu A/cm(2)), high emission current density (similar to 1288 A mu A/cm(2) at 3.9 V/A mu m) and superior current stability (similar to 4.5 h for similar to 1 A mu A) compare to pristine PbBi2Se4 emitter. Thus, the facile one step synthesis approach and robust nature of rGO-PbBi2Se4 composite emitter can provide prospects for the future development of large-area emitter applications such as flat-panel-display and vacuum micro/nanoelectronics devices.

Probing the effect of selenium substitution in kesterite-Cu2ZnSnS4 nanocrystals prepared by hot injection method - Pandharkar, Subhash; Rondiya, Sachin; Bhorde, Ajinkya; Nair, Shruthi; Aher, Rahul; Vairale, Priti; Waghmare, Ashish; Naik, Dhirsing; Waykar, Ravindra; Jadhav, Yogesh (Journal of Materials Science-Materials in Electronics, 2019)
In this paper, we report the effect of sulfur (S) substitution with selenium (Se) in CZTS nanocrystals prepared by hot injection method. The formation of kesterite-copper zinc tin sulfide (Cu2ZnSnS4, CZTS) and copper zinc tin selenide (Cu2ZnSnSe4, CZTSe) nanocrystals is confirmed by X-ray diffraction (XRD), Raman spectroscopy and transmission electron microscopy (TEM) analysis. The XRD, TEM and atomic force microscopy (AFM) analysis shows an overall increase in average crystallite size upon Se substitution. AFM images revealed an increase in root mean square surface roughness (S-q) and average surface roughness (S-a) when S in CZTS is replaced by Se. The substitution of S by Se in host CZTS narrows the optical band gap from 1.56 to 1.03 eV. The ultraviolet photoelectron spectroscopy (UPS) analysis shows shift in valence band and conduction band edge in CZTSe compared to CZTS. The photocurrent density measurement in synthesized CZTSe thin films is similar to 4 to 5 times higher than CZTS thin films. The obtained results show that CZTSe can be a promising candidate as absorber material in photovoltaic applications.

Solvothermal growth of PbBi2Se4 nano-flowers: a material for humidity sensor and photodetector applications - Aher, Rahul; Bhorde, Ajinkya; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Naik, Dhirsing; Vairale, Priti; Karpe, Smita; Late, Dattatray; Prasad, Mohit; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2019)
In the present work, lead bismuth selenide (PbBi2Se4) nano-flowers are synthesized by using a simple solvothermal method. Humidity sensor and photodetector based on PbBi2Se4 nano-flowers are fabricated on indium tin oxide (ITO) substrates and their sensing properties are investigated. Formation of PbBi2Se4 is confirmed by XRD, EDS, and XPS whereas formation of nano-flowers is confirmed by SEM and TEM analysis. XRD analysis reveals the hexagonal crystal structure of PbBi2Se4 phase with a = b = 4.22 angstrom, and c= 17.42 angstrom. The surface morphology of PbBi2Se4 clearly shows the formation of well-organized flower-like nanostructures which closely resembles the shape of Dahlia. The elemental mapping of chemical constituents obtained from SEM-EDS analysis shows uniform distribution of chemical constituents for the Pb, Bi, and Se in PbBi2Se4 nano-flowers. The PbBi2Se4 nano-flowers based humidity sensor has a typical response time of approximate to 65s and recovery time of approximate to 75 s. In case of PbBi2Se4 nano-flowers-based photodetector, the response and recovery time are observed approximate to 121 and approximate to 123 s, respectively, under visible light illumination with photoresponsivity (5 x 10(-6)), photosensitivity (2.16%), and quantum efficiency (1.5 x 10(4)). The obtained results demonstrate the potential applications of solvothermally grown PbBi2Se4 nano-flowers-based devices for humidity sensors and photodetectors. The ease of the present work is to develop novel material to obtain device quality humidity sensors and photodetectors.
Keywords: humidity sensor; PbBi2Se4; photodetector; XPS; XRD